Hocus pocus - Vonnegut, Kurt 1922-2007 (Putnam, 1990)
A small, exclusive college in upstate New York is nestled along the frozen shores of Lake Mohiga . . . and directly across from a maximum-security prison. The two institutions manage to coexist peacefully, until 10,000 prisoners break out and head directly for the college.
Keywords: Prisoners -- Fiction; Satire